2015
DOI: 10.4314/mmj.v27i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of maternal mortality among critically ill obstetric patients

Abstract: AimEvaluation of the predictors of maternal mortality among critically ill obstetric patients managed at the intensive care unit (ICU). MethodsA case control study to evaluate the predictors of maternal mortality among critically ill obstetric patients managed at the intensive care unit (ICU) of the University of Ilorin Teaching Hospital, Ilorin, Nigeria from 1st January 2010 to 30th June 2013. Participants were critically ill obstetric patients who were admitted and managed at the ICU during the study period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 12 publications
3
23
0
1
Order By: Relevance
“…In one report, most maternal deaths followed coagulation and respiratory dysfunction; however, most preventable maternal deaths were from obstetric complications . Fatality in critically ill obstetric patients has been reported to depend on the clinical state at admission to intensive care . Most women in low‐resource countries present late without referral note and are transported in poor conditions without provision for care in transit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one report, most maternal deaths followed coagulation and respiratory dysfunction; however, most preventable maternal deaths were from obstetric complications . Fatality in critically ill obstetric patients has been reported to depend on the clinical state at admission to intensive care . Most women in low‐resource countries present late without referral note and are transported in poor conditions without provision for care in transit.…”
Section: Discussionmentioning
confidence: 99%
“…Fatality in critically ill obstetric patients has been reported to depend on the clinical state at admission to intensive care . Most women in low‐resource countries present late without referral note and are transported in poor conditions without provision for care in transit. Often, health facilities are poorly sited, 68% of women in this study live far from the facilities.…”
Section: Discussionmentioning
confidence: 99%
“…State of consciousness and the presence of a fever were associated with the occurrence of maternal death in the present study; whereas a 2014 Kenyan study by Yego et al [29] showed that the presence of fever was not associated with the occurrence of maternal death. Studies have shown that hemorrhage, septicemia, and eclampsia/pre‐eclampsia are the most common causes of death [6,23,29] and can influence the state of consciousness [30]. This raises the capacity of health facilities to support women in cases of obstetric complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. First, the retrospective design limited the availability of some clinically relevant variables such as parity, details on antenatal care, socio-economic information and foetal outcomes that were not collected in HDU charts (29). Secondly, although reason for admission in HDU…”
Section: Discussionmentioning
confidence: 99%